Handbook of feminist governance - Sawer, Marian 1946-; Banaszak, Lee Ann 1960-; True, Jacqui; Kantola, Johanna 1977- (Edward Elgar Publishing, 2023)
Compiling state-of-the-art research from 58 leading international scholars, this dynamic Handbook explores the evolution of feminist analytical and organising principles and their introduction into governance institutions in national, regional and global settings.
Keywords: Electronic books